Limiting factors in the process of preparing a scientific research Project - Huaman Huayllas, Pilar (2019)
Objective. To identify limiting factors in the process of preparing a scientific research project in students of the nursing program at Universidad de Huanuco, 2019. Methods. It was an observational, prospective, and analytical study. Population sample comprised of 60 students. Measurement instruments were: interview guide with general characteristics of the sample. Two questionnaires, preparation of a research project and limiting factors, which were validated. For the statistical analysis, Chi-Square test of independence was used, Odds ratio (OR) estimation and p < 0.05 were performed. Results. Project preparation process in 53.3 % (32) was adequate. When contrasting hypotheses it was found that the individual factors: disinterest for contributing to the solution of a problem and/ or needs through research, the no development of critical thinking, little habit of reading scientific articles, little commitment for project preparation, disinterest in scientific research, insufficient knowledge to search for scientific information, little command Word and other computer programs, lack of storage media and/or information devices and lack of internet access. Institutional factors: low interaction with the tutor to answer questions about preparing a project, ignorance of the topic by the thesis advisor and perception of lack of teaching methodologies skills to advise projects. All of these were significant in the preparation process of the scientific research project. Conclusion. Findings highlight predominance of individual factors as limiting factors in the process of elaboration of the scientific project.